Acceso, uso y calidad del financiamiento que reciben las Mipymes - Herrera Herrera, Wilmer Hernan (2023)
This work is oriented to research about the access, use and quality of financing of MSMEs, as a case: the urban area of ​​the city of Latacunga, with the purpose of knowing in depth the process of financial inclusion in this important sector of the economy and the influence of these dimensions in the development of MSMEs. For this, in the first instance, the referential theoretical framework was established, the same one that had certain difficulties, since there is not much bibliographic availability about this topic, in addition to the studies carried out by international credit and social assistance organizations.